2015
DOI: 10.1175/jpo-d-14-0030.1
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Turbulence under Hurricane Gustav (2008)

Abstract: Extreme winds and complex wave fields drive upper-ocean turbulence in tropical cyclone conditions. Motivated by Lagrangian float observations of bulk vertical velocity variance (VVV) under Hurricane Gustav (2008), upper-ocean turbulence is investigated based on large-eddy simulation (LES) of the wave-averaged Navier-Stokes equations. To realistically capture wind-and wave-driven Langmuir turbulence (LT), the LES model imposes the Stokes drift vector from spectral wave simulations; both the LES and wave model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…While numerous studies have shown that Stokes production is often a dominant term in the TKE budget during times when Langmuir turbulence is present (McWilliams et al 2012;Rabe et al 2015), an analysis of the TKE budget on this dataset indicates that the pressure work was the dominant transport term and balanced dissipation to first order in the surface layer of the estuary (Scully et al 2016). More detailed analysis of turbulent energetics observed during this experiment can be found in Scully et al (2016;A.…”
Section: August 2017 F I S H E R E T a Lmentioning
confidence: 83%
See 1 more Smart Citation
“…While numerous studies have shown that Stokes production is often a dominant term in the TKE budget during times when Langmuir turbulence is present (McWilliams et al 2012;Rabe et al 2015), an analysis of the TKE budget on this dataset indicates that the pressure work was the dominant transport term and balanced dissipation to first order in the surface layer of the estuary (Scully et al 2016). More detailed analysis of turbulent energetics observed during this experiment can be found in Scully et al (2016;A.…”
Section: August 2017 F I S H E R E T a Lmentioning
confidence: 83%
“…It has been shown that Langmuir turbulence cells align predominantly with vertical shear in the Lagrangian velocity, defined as the sum of the Eulerian velocity and the Stokes drift velocity associated with wave orbital velocities. This shear strains the vorticity field generated beneath breaking waves (Leibovich 1983;McWilliams et al 1997;Van Roekel et al 2012;Rabe et al 2015). Therefore, the relative roles of breaking impulses and mean total shear in determining the stress direction in the surface layer of the estuary can be qualitatively addressed using the observed directions of wave breaking, Lagrangian shear, and the Reynolds stress in the surface layer of the estuary.…”
Section: August 2017 F I S H E R E T a Lmentioning
confidence: 99%
“…where the model variables are SGS averaged, D/Dt 5 ›/›t 1 u Á ›/›x, x is the coordinate vector, u is the velocity vector, u S is the Stokes drift vector (the vertical component is set to 0), f is the Coriolis parameter, p is the generalized pressure [p/r 1 0.5(ju 1 u S j 2 2 juj 2 )], p is the pressure, and SGS are the subgrid-scale terms described in detail by Rabe et al (2015). Scalar (temperature) distribution is solved by the advectivediffusive equation:…”
Section: March 2016mentioning
confidence: 99%
“…The LES results suggest that such a regime may be due to large variability of the Langmuir turbulence, since the local wave field varies significantly (both in time and in space) under a tropical cyclone. Comparisons between the turbulent quantities from the LES and the observations are imperfect for various reasons, particularly because of uncertainty of the drag coefficient in tropical cyclone conditions (see Rabe et al 2015). Nevertheless, the results suggest that the Langmuir turbulence is an important, spatially variable source of mixing under a tropical cyclone and that the additional mixing due to the CL vortex force is necessary to best match the simulations and the field observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation